2010
DOI: 10.1002/ange.200904638
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergente Organokaskadenreaktionen

Abstract: In der Synthese von Naturstoffen spielen Kaskadenreaktionen eine gewichtige Rolle, allerdings sind sie nur in wenigen Fällen bezüglich ihrer Effektivität und Eleganz vergleichbar zu enzymkatalysierten Vorbildern. Die Lehrmeisterfunktion der Natur ist hier noch über weite Bereiche intakt. Literaturbekannte Naturstoffsynthesen sind auch heute noch oft durch langwierige, zeitaufwändige und vielstufige Synthesebemühungen charakterisiert. Es ist daher nicht überraschend, dass die Verwendung von Enzymen in der organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 26 publications
(24 reference statements)
0
9
0
1
Order By: Relevance
“…With respect to stereocontrol, enantioselective catalysis, and more specifically, the proven ability of chiral secondary amines 3 to promote cascade reactions using enals as Michael acceptors, through the combination of the nowadays well established iminium and enamine activation manifolds is a good example of the high level of sophistication achieved by this chemistry. 4 …”
Section: Introductionmentioning
confidence: 99%
“…With respect to stereocontrol, enantioselective catalysis, and more specifically, the proven ability of chiral secondary amines 3 to promote cascade reactions using enals as Michael acceptors, through the combination of the nowadays well established iminium and enamine activation manifolds is a good example of the high level of sophistication achieved by this chemistry. 4 …”
Section: Introductionmentioning
confidence: 99%
“…[3] Thus, great attention has been drawn to the development of efficient methods to build these spirocyclic systems. [4] In the past decades, phosphine-catalyzed domino reactions [5] have become a powerful tool in the construction of carbo-and heterocycles. [6] While electron-deficient alkenes [7] and alkynes [8] have been well studied, little attention has been paid to ynone derivatives in organocatalytic domino reactions.…”
mentioning
confidence: 99%
“…Initially, we carried out the reaction of ynone 1 a with 2arylideneindane-1,3-dione 2 a in CHCl 3 in the presence of benzoic acid (30 mol %) by using 10 mol % phosphine as catalyst. Encouragingly, the annulation product 3 a was isolated in 74 % yield ( [3][4][5]. Solvent screening revealed that the solvent significantly affected the reaction performance (Table 1, entries 6-10).…”
mentioning
confidence: 99%
“…With the various recently developed organocatalytic activation modes at hand, including the concept of bifunctional organocatalysts and multicatalytic systems, [187] numerous novel cascade sequences can be envisaged with a tendency from simple domino reactions to triple and even quadruple domino reactions in cascade. [188] Undoubtedly, the future direction in this emerging field is to continue expanding the scope of organocatalytic domino reactions through the identification of novel modes of reactivity and to apply these powerful strategies to the synthesis of biologically interesting molecules including natural products.…”
Section: Discussionmentioning
confidence: 99%